Penatagunaan Lahan Dusung Bagi Pengembangan Agrowisata di Lata-Negeri Hative Besar Sesuai RTRW Kota Ambon - Trivena Uspessy; Conradus Ufie; Rudi Soplanit (Fakultas Pertanian, Universitas Pattimura, 2022)
This study aims to: 1) describe the land use of the hamlet in Lata, the components of plant species, and the uniqueness of cultivation, 2) identify the characteristics/quality of land and the environment in Lata, 3) evaluate the suitability of the hamlet land use/agroforest for the development of agro-tourism. This research was carried out using an analytical method at the transect location in the Kampong Lata area. The results of the study include: 1) Dusung land use or hamlet land systems/compositions (hamlet types) in the Lata Hative Besar petuanan, from the coast to the mountains include hamlets of the type of hamlets, village yards, beaches and hamlets of heirlooms (covering hamlets). king), dusung dati (from the Uspessy, Lakatua, and Siatau clans), and hamlets of the country, 2) Evaluation of the suitability of hamlet/agroforest land use for the development/regulation of agro-tourism according to the direction of the Ambon City RTRW 2011-2031, shows that dusung dati/agrosilviculture are appropriate and a priority for development of agro-tourism, following the hamlet of the yard/homegarden, following the hamlet of the beach/agrosilvifishery. Prioritization here is not only seen from the suitability and biophysical characteristics of the land for components of relevant plant species that support agro-tourism, but also from the attractiveness of historical values ​​and various distinctive local cultures/wisdoms as a whole and can increase the income/welfare of local residents who sustainable.